Metode Pendidikan Islam Bagi Anak Dalam Keluarga Single Mother Di Desa Timbuseng Kecamatan Pattallassang Kabupaten Gowa - Rusmiati; Hasyim Asy’ari; Ardiyansyah (4, 2026)
This study aims to describe and analyze Islamic education methods for children in single-mother families in Timbuseng Village, Pattallassang District, Gowa Regency. The background of this research is based on the social reality of the increasing number of single-mother families, who are often perceived as having limitations in carrying out educational functions, particularly Islamic religious education for children. This study uses a qualitative approach with a descriptive research method. Data collection techniques were conducted through observation, in-depth interviews, and documentation with key informants, single mothers, and supporting informants such as children, community leaders, and local religious leaders. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and techniques. The results indicate that the Islamic education methods applied in single-mother families in Timbuseng Village include exemplary behavior (uswah hasanah), habituation (ta'wid), advice (mau'izhah), and proportional supervision and discipline. A mother's exemplary conduct in performing religious duties, maintaining morals, and instilling Islamic values ​​are key factors in shaping a child's religious character. Although single mothers face various challenges such as limited time, economic pressures, and social stigma, these do not prevent the effective implementation of Islamic education. This study concludes that the quality of Islamic education in single-mother families is determined more by the mother's consistency, sincerity, and commitment as the primary educator than by the completeness of the family structure. Thus, single-mother families have significant potential in shaping a generation of faithful, noble morals, and strong personalities. Abstrak Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis metode pendidikan Islam bagi anak dalam keluarga single mother di Desa Timbuseng, Kecamatan Pattallassang, Kabupaten Gowa. Latar belakang penelitian ini didasarkan pada realitas sosial meningkatnya jumlah keluarga single mother yang kerap dipersepsikan memiliki keterbatasan dalam menjalankan fungsi pendidikan, khususnya pendidikan agama Islam bagi anak. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi dengan informan utama para ibu single mother serta informan pendukung seperti anak, tokoh masyarakat, dan tokoh agama setempat. Analisis data menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diuji melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa metode pendidikan Islam yang diterapkan dalam keluarga single mother di Desa Timbuseng meliputi metode keteladanan (uswah hasanah), pembiasaan (ta‘wid), nasihat (mau‘izhah), serta pengawasan dan pendisiplinan yang proporsional. Keteladanan ibu dalam menjalankan ibadah, menjaga akhlak, dan menanamkan nilai-nilai keislaman menjadi faktor utama dalam membentuk karakter religius anak. Meskipun para ibu single mother menghadapi berbagai tantangan seperti keterbatasan waktu, tekanan ekonomi, dan stigma sosial, hal tersebut tidak menghalangi terlaksananya pendidikan Islam secara efektif. Penelitian ini menyimpulkan bahwa kualitas pendidikan Islam dalam keluarga single mother lebih ditentukan oleh konsistensi, ketulusan, dan komitmen ibu sebagai pendidik utama dibandingkan dengan kelengkapan struktur keluarga. Dengan demikian, keluarga single mother memiliki potensi yang signifikan dalam membentuk generasi yang beriman, berakhlak mulia, dan berkepribadian kuat.